Understanding and Responding to Adolescent Girls’ Online Cruelty - Sokal, Laura (Canadian Journal of Counselling and Psychotherapy, 2012)
Many school counsellors have identified “cyber-bullying” among adolescent girls as a growing concern. In order to respond to this issue, this article begins with a new model of cyber-communications from the unique perspective of adolescent girls. Next, it explores the limitations of responding to this model, based on current understandings of cyberbullying. Finally, based on the current literature, recommendations are made to school counsellors regarding the essential components of programming that show promise in addressing online cruelty among this group.